2023
DOI: 10.3390/v15061285
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Lumpy Skin Disease Virus Transmission from Subclinically Infected Cattle by Stomoxys calcitrans

Abstract: Lumpy skin disease virus (LSDV) is a vector-transmitted capripox virus that causes disease in cattle. Stomoxys calcitrans flies are considered to be important vectors as they are able to transmit viruses from cattle with the typical LSDV skin nodules to naive cattle. No conclusive data are, however, available concerning the role of subclinically or preclinically infected cattle in virus transmission. Therefore, an in vivo transmission study with 13 donors, experimentally inoculated with LSDV, and 13 naïve acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…The present study follows up on the research on recombinant strains detected in Russia and provides further evidence confirming that the RVLSs of LSDV employ alternative mechanisms of transmission in contrast to that of Cluster 1.2 strains. Moreover, this is the first study to report that subclinically affected animals transmit LSDV to animals sharing the same airspace in an insect-proof facility, which is contrary to the findings of Heageman et al ( 41 ). Subclinical infection is a typical manifestation of LSDV, and the efficiency of its control measures is directly linked to the manner whereby virus-carrying animals, regardless of the clinical or subclinical manifestation of the disease in an outbreak zone, are identified and managed ( 22 , 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study follows up on the research on recombinant strains detected in Russia and provides further evidence confirming that the RVLSs of LSDV employ alternative mechanisms of transmission in contrast to that of Cluster 1.2 strains. Moreover, this is the first study to report that subclinically affected animals transmit LSDV to animals sharing the same airspace in an insect-proof facility, which is contrary to the findings of Heageman et al ( 41 ). Subclinical infection is a typical manifestation of LSDV, and the efficiency of its control measures is directly linked to the manner whereby virus-carrying animals, regardless of the clinical or subclinical manifestation of the disease in an outbreak zone, are identified and managed ( 22 , 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, not only the clinical form of LSDV has gained research interest but also the subclinical manifestation has been recognized as a distinctive characteristic of LSDV ( 41 ). With the recent emergence of recombinant vaccines, such as strains exhibiting transmission without arthropod activity ( 31 , 32 ), efforts have been made to determine the contribution of all forms.…”
Section: Discussionmentioning
confidence: 99%
“…The nodules may occur all over the body and may become necrotic, thus providing a pathway for secondary infections. Importantly, a significant part of the infected animals remains subclinical [ 8 ], but these animals may nevertheless contribute to transmission of the disease [ 9 ]. The morbidity rate ranges from 5 to 45% [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arthropod vectors primarily transmit LSDV. Studies have demonstrated that Aedes aegypti mosquitoes 1 , Stomoxys calcitrans 2 , and Haematopota spp . biting flies can mechanically transmit LSDV 3 .…”
Section: Introductionmentioning
confidence: 99%